2020
DOI: 10.11604/pamj.2020.36.240.24088
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal rhythm of blood pressure among Nigerians with hypertension using 24-hour ambulatory blood pressure monitoring

Abstract: Introduction hypertension is the most common cardiac disease in Nigeria. There are very limited studies in Nigeria on the use of 24-hour ambulatory blood pressure monitoring (24-h ABPM) for evaluation of hypertensive patients. Twenty four-hour ABPM, unlike office blood pressure (OBP), can assess diurnal variation using parameters like awake blood pressure (BP), asleep (nocturnal) BP, mean 24-hour BP and dipping pattern. This can help in assessment of increased cardiovascular risk and management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In this study, the non-dipping pattern was the most prevalent abnormality of diurnal BP variation in our patients with newly diagnosed hypertension, which is similar to previous studies (11,19). We have shown that patients with the reverse dipping pattern had the lowest mitral E/A ratio, hence they were at greatest risk of diastolic dysfunction and hypertension-mediated organ damage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the non-dipping pattern was the most prevalent abnormality of diurnal BP variation in our patients with newly diagnosed hypertension, which is similar to previous studies (11,19). We have shown that patients with the reverse dipping pattern had the lowest mitral E/A ratio, hence they were at greatest risk of diastolic dysfunction and hypertension-mediated organ damage.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study revealed that night-time dosing with antihypertensive medications reduced major cardiovascular events such as CVD death, stroke and myocardial infarction by 67%, probably because of night-time BP attenuation effect (6). Some local studies done, were mostly on the prevalence of circadian rhythm in patients with hypertension (11)(12)(13), but there is a dearth of studies on the association between blood pressure dipping patterns and hypertension-mediated organ damage among patients with hypertension. Hence, this study determined the association between BP dipping patterns and hypertensionmediated organ damage among Nigerian patients with newly-diagnosed hypertension.…”
Section: Introductionmentioning
confidence: 99%